SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN TALENTTERBAIK PROGRAM BAKTI MILENIAL #5MENGGUNAKAN METODE MOORA - Ahmad Kayyis (2024)
The natural wealth contained in the vast waters of Indonesia has the potential to be utilized and maximized by coastal communities. According to the Ministry of Maritime Affairs and Fisheries (KKP), 62% of the territory that contains Indonesia is water, with an ocean area of 6.32 million square kilometers and a land area of 1.91 million square kilometers. Bakti Millennial exists as a forum for developing coastal villages through community service activities. To improve the quality of the Bakti Millennial program, the marketing strategy used must be considered and evaluated continuously. This research aims to improve one of the marketing strategy support systems for the Bakti Millenial program by implementing a decision support system for selecting the best talent for the Bakti Millenial #5 Wakatobi program. The assessment criteria used concern 7 aspects of the criteria used in selection. To support the decision support system, the MOORA method was chosen as the method to be used. The choice of this method is due to the flexibility it has in taking into account weighted or unweighted criteria, so that it can maximize the proposed system. The results of the research carried out are the modeling of the Talent Management decision support system for the Bakti Millennial program. Keywords: Decision Support System, MOORA Method, Millennial Service, Talent Management